In vitro Shoot Regeneration from Crown and Sucker Explants of Ananas comosus cv. Josapine - Dahmendra Sriskanda; Soo Ping Khor; Li Vern Tan; Sreeramanan Subramaniam; Nurulhikma Md Isa; Bee Lynn Chew (Tropical Life Sciences Research, 2025)
Pineapple, Ananas comosus (L.) Merr., is a highly nutritious, major tropical Amazonian fruit valued for its health properties. Josapine, a successfully commercialised Malaysian hybrid, bears sweet fruits and has a shorter gestation period as compared to other cultivars. The current study aims to evaluate the in vitro regeneration and shoot multiplication potential of Ananas comosus cv. Josapine using different types of explant sources and different concentrations of cytokinins. Pineapple crown and suckers were surface sterilised and cultured in MS medium supplemented with 6-Benzylaminopurine (BAP) at different concentrations (0.0 mg/L, 1.0 mg/L, 2.0 mg/L and 3.0 mg/L) for six weeks to evaluate the shoot regeneration efficiency of both explants used. In vitro induced shoots from crown and sucker explants were also cultured in different concentrations of BAP and kinetin (0.0 mg/L, 0.5 mg/L, 1.0 mg/L, 1.5 mg/L, 2.0 mg/L, 2.5 mg/L and 3.0 mg/L) for the induction of multiple shoots and roots. Results from the current study revealed that the highest percentage of shoot induction obtained from crown explants was 88.00% in the treatment of 2.0 mg/L BAP (3.50 ± 0.67 shoots per explant), whereas the treatment of 3.0 mg/L BAP resulted in the highest percentage of shoot induction (82.00%) from sucker explants. As for the response of in vitro shoots, the treatment of 2.0 mg/L BAP resulted in the highest number of shoots (6.85 ± 0.61 shoots per explant), whereas the highest number of roots (6.09 ± 0.46 roots per explant) was observed in MS media supplemented with 1.5 mg/L kinetin after 16 weeks of culture. This study demonstrates methods for in vitro shoot multiplication suitable for the micropropagation and commercialisation of the Josapine cultivar. This facilitates the mass production of disease-free, high-quality planting materials, leading to improved fruit quality and enhanced export potential of this pineapple cultivar.